2000
DOI: 10.1093/ajcn/71.2.507
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A supplementation selectively improves the linear growth of Indonesian preschool children: results from a randomized controlled trial

Abstract: High-dose vitamin A supplementation improves the linear growth of children with very low serum retinol and the effect is modified by age and breast-feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
1
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 18 publications
2
56
1
10
Order By: Relevance
“…16,26 In comparison with the neighboring countries in Southeast Asia, a higher prevalence of VAD (serum retinol concentration < 0.70 μmol/L) was reported among children in rural regions of southern Vietnam and along the southern coast of central Java in Indonesia. 10,27 During the 1990s, Indonesia showed good progress in reducing VAD but the prevalence of the transition changed after the tsunami disaster of 2004 that killed more than 200,000 persons in the territories of Ache, Nias, and Sumatra. This disaster, together with poverty, propagated the prevalence of health problems, including VAD, among children.…”
mentioning
confidence: 99%
“…16,26 In comparison with the neighboring countries in Southeast Asia, a higher prevalence of VAD (serum retinol concentration < 0.70 μmol/L) was reported among children in rural regions of southern Vietnam and along the southern coast of central Java in Indonesia. 10,27 During the 1990s, Indonesia showed good progress in reducing VAD but the prevalence of the transition changed after the tsunami disaster of 2004 that killed more than 200,000 persons in the territories of Ache, Nias, and Sumatra. This disaster, together with poverty, propagated the prevalence of health problems, including VAD, among children.…”
mentioning
confidence: 99%
“…The lack of effect of vitamin A on ponderal growth but the presence of an effect on linear growth was probably due to the fact that vitamin A deficiency was not severe enough to be a growth-limiting factor in this population. Vitamin A supplementation does improve ponderal growth in severely vitamin A-deficient (Hadi et al, 2000) and xerophthalmic (West et al, 1997) children.…”
Section: Complex Interactions With Infection and Diet H Hadi Et Almentioning
confidence: 98%
“…Among those articles reporting a positive effect, some noted that the effect was greater in children Z2 y (Muhilal et al, 1988;Hadi et al, 2000), and in non-breastfed children (Hadi et al, 2000). Furthermore, the positive effect of vitamin A supplementation on growth was restricted to children with low serum retinol concentrations (Hadi et al, 2000) or children with xerophthalmia (West et al, 1997), and was only observed in summer (Bahl et al, 1997) or the late dry season (West et al, 1997). The strongest effect was found in the late dry season (Hadi et al, 2002), while the least effect (Hadi et al, 2002) or a slightly negative effect (West et al, 1997) of vitamin A supplementation on growth was found during winter.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations